Climate change and agronomic management: Addressing wheat yield gaps and sustainability challenges in the Mediterranean and MENA regions - Tita, Davide; Mahdi, Karrar; Devkota, Krishna; Devkota Wasti, Mina Kumari (Elsevier Masson, 2025)
Wheat is a crucial crop for food and nutritional security in Mediterranean and MENA regions, yet it faces significant challenges due to high yield variability, low average productivity, and substantial yield gaps. This highlights the urgent need for improved agricultural practices to enhance its productivity and resilience. The region's climate climate change, soil degradation, and water supply variability significantly impact wheat production, requiring innovative and integrated solutions to minimize yield gaps and improve sustainability.